Longitudinal community plasma HIV-1 RNA concentrations and incidence of HIV-1 among injecting drug users: prospective cohort study. (30th April 2009) - Wood, Evan; Kerr, Thomas; Marshall, Brandon D L; Li, Kathy; Zhang, Ruth; Hogg, Robert S; Harrigan, P Richard; Montaner, Julio S G
Abstract : Objective To examine the relation between plasma HIV-1 RNA concentrations in the community and HIV incidence among injecting drug users. Design Prospective cohort study. Setting Inner city community in Vancouver, Canada. Participants Injecting drug users, with and without HIV, followed up every six months between 1 May 1996 and 30 June 2007. Main outcome measures Estimated community plasma HIV-1 RNA in the six months before each HIV negative participant's follow-up visit. Associated HIV incidence. Results Among 622 injecting drug users with HIV, 12 435 measurements of plasma HIV-1 RNA were obtained. Among 1429 injecting drug users without HIV, there were 155 HIV seroconversions, resulting in an incidence density of 2.49 (95% confidence interval 2.09 to 2.88) per 100 person years. In a Cox model that adjusted for unsafe sexual behaviours and sharing used syringes, the estimated community plasma HIV-1 RNA concentration remained independently associated with the time to HIV seroconversion (hazard ratio 3.32 (1.82 to 6.08, P<0.001), per log10 increase). When the follow-up period was limited to observations after 1 January 1988 (when the median plasma HIV RNA concentration was <20 000 copies/ml), the median viral load was no longer statistically associated with HIV incidence (1.70 (0.79 to 3.67, P=0.175), per log10 increase). Conclusions A longitudinal measure of community plasma HIV-1 RNA concentration was correlated with the community HIV incidence rate and predicted HIV incidence independent of unsafe sexual behaviours and sharing used syringes. If these findings are confirmed, they could help to inform both HIV prevention and treatment interventions.